The drift of the city - Jarauta, Francisco (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2020)
Since the 1990’s, the tendency towards an increasingly stronger globalization and the defense of the local as space and framework of a basic identification is establishing the characterization of a new society and a new culture. In this context, the focus of the debate of architecture is no longer self-referential and it has become one of the laboratories for more active analysis and discussion relating to the contemporary debate about the great ongoing civilizing changes that humanity is experiencing. This text includes some reflections on the emergence of new problems mainly resulting from the growth of global population and its urban distribution. From this perspective, some proposals for city models are discussed, specifically, from the second half of the 20th century―although references to masters of modernity and more recent models are also included―understanding the city as the expression of new social, cultural and political tensions of the modern world.
Keywords: Globalization; Deterritorialization; Generic city; Population growth